Relocation and Recolonization of Coho Salmon in Two Tributaries to the Elwha River: Implications for Management and Monitoring. Issue 5 (18th April 2017) - Liermann, Martin; Pess, George; McHenry, Mike; McMillan, John; Elofson, Mel; Bennett, Todd; Moses, Raymond
Abstract: In 2012 the lower of two Elwha River dams was breached, restoring access of anadromous salmonids to the middle Elwha River (between the two dams), including two distinct tributaries, Indian Creek and Little River. While comparable in size, Indian Creek is considerably less steep than Little River (mean slope of 1.0% versus 3.5%, respectively) and has a warmer stream temperature regime due to its source, Lake Sutherland. During and after breaching, Coho Salmon Oncorhynchus kisutch were relocated to these tributaries from lower Elwha River hatcheries (below the dams) to determine if individuals from a hatchery‐dominated population would successfully spawn and seed the systems with juveniles and to assess differences in recolonization between the streams. Transplantation led to immediate spawning, which resulted in levels of smolt out‐migrants per stream kilometer comparable with other established Coho Salmon populations in the Pacific Northwest. During the first 2 years of the relocation, redd densities in the two systems were similar but Indian Creek produced four to five times as many smolts per kilometer as Little River. In addition, fry out‐migration occurred 2 to 4 weeks earlier in Indian Creek, as predicted by the warmer incubation temperatures. In the first years of the study, there was little evidence of natural colonization of the two tributaries by adults. However, in 2016 over half of the observed adults returning to the two tributaries were not transplanted, suggesting that the progeny from the transplanted fish were returning to their natal waters. This work demonstrates that transplanting hatchery‐dominated Coho Salmon adults into newly available habitat can result in immediate freshwater production that is comparable to other systems and that density and timing of juvenile out‐migrants can differ dramatically based on the seeded habitat. Received December 9, 2016; accepted March 30, 2017 Published online July 28, 2017